Navigating Emergency Online Learning: A Comparative Study of University Students in Bangladesh and Indonesia During the COVID-19 Pandemic - Imam Fitri Rahmadi; Sanjida Akter Tanni; Sabbir Ahmed Chowdhury; Fadhlan Muchlas Abrori; Yudi Yunika Putra; Sasih Karnita Arafatun; Ratnasari Dyah Utami; Akhmad Syakir (Universitas Muhammadiyah Surakarta, 2024)
The present study compares the university student’s experiences of learning in virtual mode during unprecedented impacts of the COVID-19 in Bangladesh and Indonesia with a focus on the enjoyment, performance, satisfaction, and cost of online learning.This was quantitative cross-sectional research conducted by using an online survey with the participation of 438 and 529 university students in Bangladesh and Indonesia. The findings reveal that university students in Bangladesh have little more comfortable with online learning compared to those in Indonesia. The students in both countries have no problem with adaptation to avant-garde online learning platforms. University students in Bangladesh appear little more satisfied with online teaching while those in Indonesia tend to be less satisfied. University students either in Bangladesh or in Indonesia consider online learning as an expensive learning mode. The present study depicts an early online remote learning experience of university students during the COVID-19 pandemic. Due to the nature of the descriptive comparative study focusing on Bangladesh and Indonesia, the results of this study may not be generalised. Specific factors underlying their experiences are in need of further investigation. In future endeavours, lectures are urged to actively harness proper technologies, mix between conventional and virtual learning or blend synchronous and asynchronous learning to provide more enjoyable and interesting online learning thus the students can be more satisfied.